L’amic, prova’l primer ans que l’hages menester: Fonts clàssiques d’un refrany català inclòs en la Paremiologia catalana comparada de Sebastià Farnés - Pascual-López, Xavier (Studia Romanica Posnaniensia, 2016)
This paper aims to investigate the Classical proverbs listed as equivalents to the Catalan proverb L’amic, prova’l primer ans que l’hages menester by Sebastià Farnés in his volume entitled Paremiologia catalana comparada. In this paper, I will establish these Classical proverbs’ sources, consider their authenticity and correspondence with this Catalan proverb, and increase the number of Classical sources, since this Catalan proverb bears witness to its Classical tradition and is related to philosophical and literary passages that can be considered as previous manifestations of this tradition. These Greek and Latin passages are compiled and compared so as to determine the different ways in which the idea included in this Catalan proverb was expressed over time. The conclusion is that the consideration about friendship presented by this proverb is embedded into a long textual/ideological tradition which ultimately refers to the sage Solon, the poet Theognis and the philosopher Theofrast, although there may be connections with the Judeo-Christian tradition as well.